2007
DOI: 10.1210/en.2007-0014
|View full text |Cite
|
Sign up to set email alerts
|

Peroxisome Proliferator-Activated Receptor α Protects against Obesity-Induced Hepatic Inflammation

Abstract: Recently it has become evident that obesity is associated with low-grade chronic inflammation. The transcription factor peroxisome proliferator-activated receptor ␣ (PPAR␣) has been shown to have a strong antiinflammatory action in liver. However, the role of PPAR␣ in obesity-induced inflammation is much less clear. Therefore, the aim of our study was to determine whether PPAR␣ plays a role in obesity-induced hepatic inflammation. To induce obesity, wild-type sv129 and PPAR␣ ؊/؊ mice were exposed to a chronic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
118
0
2

Year Published

2009
2009
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 175 publications
(131 citation statements)
references
References 36 publications
11
118
0
2
Order By: Relevance
“…As such, many PPARα target genes are involved in mitochondrial and peroxisomal β-oxidation of fatty acids [93]. Numerous studies of PPARα−/− mice have shown that fasting or high-fat feeding of these mice results in abnormal lipid accumulation in hepatocytes, which is consistent with a crucial role for PPARα in hepatic lipid metabolism [114] and [115]. In addition, in normal rats, high-fat feeding-induced steatosis was related to PPARα downregulation, presumably mediated by increased circulating free fatty acid [116].…”
Section: Peroxisome-proliferator-activated Receptors (Ppars)mentioning
confidence: 87%
See 1 more Smart Citation
“…As such, many PPARα target genes are involved in mitochondrial and peroxisomal β-oxidation of fatty acids [93]. Numerous studies of PPARα−/− mice have shown that fasting or high-fat feeding of these mice results in abnormal lipid accumulation in hepatocytes, which is consistent with a crucial role for PPARα in hepatic lipid metabolism [114] and [115]. In addition, in normal rats, high-fat feeding-induced steatosis was related to PPARα downregulation, presumably mediated by increased circulating free fatty acid [116].…”
Section: Peroxisome-proliferator-activated Receptors (Ppars)mentioning
confidence: 87%
“…Furthermore, in wild-type mice, HFD significantly increased the hepatic and adipose expression of numerous genes involved in inflammation. This effect was amplified in PPARα−/− mice and reduced in wild-type by treatment with the PPARα ligand Wy-14643, suggesting an anti-inflammatory role of PPARα in liver and adipose tissue [115]. In agreement with this, in a model of NASH, tranilast (that inhibits the action of the fibrogenic transforming growth factor-beta, TGF-β) attenuated hepatic inflammation, downregulated TNF-α expression, and up-regulated PPARα [119].…”
Section: Peroxisome-proliferator-activated Receptors (Ppars)mentioning
confidence: 97%
“…These functions may be impaired in both small and large offspring and fit in with epidemiological data indicating an increase risk of later metabolic disease in both small (Eriksson et al 2003a, 2003b, Min et al 2007 and large infants (Gillman et al 2003, Leong et al 2003, Danielzik et al 2004). PPARA has a well-documented role in hepatic lipid metabolism (Stienstra et al 2007), but its role in adipose tissue and relationship to birth weight are less clear. Previous studies investigating the role of fetal programming in the female offspring of mice fed a high unsaturated fat diet during pregnancy have demonstrated increased PPARA protein in liver along with decreased hepatic triglyceride concentrations (Zhang et al 2005).…”
Section: Pparg2 and Amentioning
confidence: 99%
“…Furthermore, it can limit interleukin (IL)-1-associated C-reactive protein expression [50,52] . In this regard, it has been shown that PPARα deficient mice are susceptible to hepatic steatosis and NASH [53][54][55] . The current concept is that PPARα activation may prevent these abnormalities [50,53] .…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, PPARα agonism reversed steatohepatitis in mice, suggesting a potential curative role against NASH [56] . This benefit might be attributed to a downregulated expression of inflammatory genes [55] . Also, PPARα activation may reverse fibrosis by reducing the expression of fibrotic markers and the number of stellate cells [56] .…”
Section: Introductionmentioning
confidence: 99%